Acoustic output levels and ultrasound output display standard - LEWIN, P. A.; NOWICKI, A. (Archives of Acoustics, 1998)
This paper discusses rationale behind the development of output display standard (ODS) and points out its clinical implications. Physical mechanisms of interaction between ultrasound and biological tissue are reviewed and basic ultrasound field parameters needed to understand and appreciate the impact of Mechanical Index (MI) and Thermal Index (TI) on clinical practice are introduced. Definition of indices is presented and their dependence on acoustic field generated by the scanning probes is discussed. The applicability of MI as an predictor of the potential mechanical effects in B-mode imaging and TI’s relevance in Doppler, M-mode and color flow imaging is indicated. Three different tissue models, namely, homogeneous and layered, and bone/tissue interface are presented in detail and the influence of each of the models on the potential temperature increase prediction is stressed. The importance of implementation of ALARA (As Low As Reasonably Achievable) principle is also noted out.